2019
DOI: 10.1186/s12943-019-1002-6
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNAs in Cancer: emerging functions in hallmarks, stemness, resistance and roles as potential biomarkers

Abstract: Circular RNAs (circRNAs) are a class of RNA molecules with closed loops and high stability. CircRNAs are abundantly expressed in eukaryotic organisms and exhibit both location-and step-specificity. In recent years, circRNAs are attracting considerable research attention attributed to their possible contributions to gene regulation through a variety of actions, including sponging microRNAs, interacting with RNA-binding proteins, regulating transcription and splicing, and protein translation. Growing evidence ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
241
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 330 publications
(249 citation statements)
references
References 180 publications
3
241
0
5
Order By: Relevance
“…15 Recent studies have shown that circRNA functions through different actions, including serving as 'miRNA sponge', regulation of transcription and splicing, interacting with RNA-binding protein, and even translating polypeptide. 16 The most extensively studied is circRNA as a competing endogenous RNA (ceRNA) to effectively sponge miRNA, for example, circ-HIPK3/miR-7 in colorectal cancer, 17 circ-EPSTI1/miR-942 in ovarian cancer, 18 circ-ANKS1B/ miR-148/152 in breast cancer 19 and circ-AMOTL1L/miR-193a-5p in prostate cancer. 20 It is well recognized that miRNA is a post-transcriptional regulator by decreasing mRNA stability or inhibiting translation via directly targeting gene 3′-UTR.…”
Section: Discussionmentioning
confidence: 99%
“…15 Recent studies have shown that circRNA functions through different actions, including serving as 'miRNA sponge', regulation of transcription and splicing, interacting with RNA-binding protein, and even translating polypeptide. 16 The most extensively studied is circRNA as a competing endogenous RNA (ceRNA) to effectively sponge miRNA, for example, circ-HIPK3/miR-7 in colorectal cancer, 17 circ-EPSTI1/miR-942 in ovarian cancer, 18 circ-ANKS1B/ miR-148/152 in breast cancer 19 and circ-AMOTL1L/miR-193a-5p in prostate cancer. 20 It is well recognized that miRNA is a post-transcriptional regulator by decreasing mRNA stability or inhibiting translation via directly targeting gene 3′-UTR.…”
Section: Discussionmentioning
confidence: 99%
“…To validate this, we determined the expression of circ_0038467 in LPS‐treated 16HBE cells, and our data demonstrated a striking upregulation of circ_0038467. Due to the closed loop structures with neither 5′ caps nor 3′ polyadenylated tails, circRNAs are resistant to RNase R . Using RNase R assays, we uncovered that circ_0038467 was indeed a circular transcript.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence suggests that circRNAs are involved in complicated functions; such as acting as endogenous RNAs to sponge miRNAs, protein decoys, protein translation, regulating expression of parental genes, modulating alternative splicing, regulating RNA-protein interactions, and acting as scaffolds in the assembly of protein complexes [12,[27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…circRNAs have been shown to be differentially regulated in human cancers, including breast, prostate, brain, bladder, colorectal, ovarian, liver and kidney as well as hematological malignancies. Thus, it is becoming increasingly clear that circRNAs have a significant role in cancer pathogenesis, and they are likely to affect several hallmarks of cancer [10,11] [12]. Understanding the functional role of circular RNA in cancer cell invasion, migration, tumor suppression provides new insights into cancer detection, oncogenesis, and cancer prevention, which is still elusive.…”
Section: Introductionmentioning
confidence: 99%